PENERAPANN METODE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN AKIDAH AKHLAK KELAS VII DI MTS RAUDLATUL ULUM NGIJO - Ayu Mimawati; Ika Ratih Sulistiani; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This study aims to determine the learning outcomes of Class VII B students at Mts Raudlatul Ulum Ngijo by using the Index Card Match method. This research is a class action research. The population of this research is 29 students of Class VII Mts Raudlatul Ulum Ngijo. The data technique used is a matter of tests, interviews, observations, and documentation the data analysis technique used is a qualitative approach. The results of this study indicate that through the application of the Index Card Match method student learning outcomes increase from pre-cycle, cycle I and cycle II. The results of the study from the first cycle showed an average value of 66. While the percentage of completion of learning reached 52%. The results of the study in the second cycle showed a value with an average value of 72. While the percentage of completion of learning reached 82.7%. Based on the results of the research cycle I and cycle II the value of students has increased the average value and also the percentage is complete.